Peran Guru PAI Dalam Mencegah Paham Radikalisme Pada Peserta Didik (Studi Kasus di SMK Addimyati Lalang, Wonojati, Kec. Jenggawah, Kabupaten Jember) - Shidqi Ahyani Shidqi (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
This research examines extreme ideas and radicalism that have spread throughout the world, including schools in Indonesia. A survey conducted from October 2010 to 2011 for students (junior and senior high schools) in Jabotabek showed that 49% of students agreed with extremist acts in the name of religion, 14.2% agreed with acts of terrorism, 84.8% of students agreed with the application of Islamic law. This study aims to analyze the role of Islamic religious education teachers in anticipating radical understanding at Addimyati Lalang Vocational School, Wonojati, Kec. Janggawah, Regent of Jember. This research is a field research with a qualitative approach. Methods of data collection is done through interviews, observation and documentation. The data obtained were analyzed deductively so as to find research conclusions. The results of the study show that the SMK in Addimyati which is under the auspices of the Islamic boarding school is also affiliated with the NU organization in its implementation. The role of Islamic religious education teachers in preventing radicalism is guiding students through extra-curricular activities, conveying religious messages with aswaja material, establishing cooperation with ustadz and pesantren caretakers.